2011
DOI: 10.4028/www.scientific.net/amm.99-100.1233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics Performance of High-Performance Concrete with Polypropylene Fibers

Abstract: The mechanics properties of HPC mixing different dosage and length of polypropylene fiber were investigated in this study. The results showed that the addition of appropriate amount and length of polypropylene fibers in HPC led to an effective improvement in the tensile strength and a little change in the compressive strength of HPC. The pronounced improvement can be attributed to the beneficial effect of polypropylene fiber on HPC by restraining the generation and development of the micro cracks in concrete, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, the dispersion efficiency of polypropylene fibers is decreased by the increasing dosage of polypropylene fibers. Therefore, the mechanical strengths remain unchanged after growing to a stable value [29][30][31]. Figure 5 shows the relationship between the mechanical strengths and the curing time of RPC with different dosage of PPFs.…”
Section: Mechanical Strengthsmentioning
confidence: 99%
“…However, the dispersion efficiency of polypropylene fibers is decreased by the increasing dosage of polypropylene fibers. Therefore, the mechanical strengths remain unchanged after growing to a stable value [29][30][31]. Figure 5 shows the relationship between the mechanical strengths and the curing time of RPC with different dosage of PPFs.…”
Section: Mechanical Strengthsmentioning
confidence: 99%
“…Polymer composites reinforced with synthetic fibers offer improved mechanical performance in engineering applications due to their strength, specific density, and light weight. Previous research has demonstrated that the addition of polypropylene fibers to composite materials can effectively control fracture and especially creep [8,9]. Among the family of this fiber, Innegra fiber is one of the newest fibers available on the market, which is made of high modulus polypropylene, which can be used independently or together with other fibers to reduce weight resist damage and improve strength.…”
Section: Introductionmentioning
confidence: 99%